Genetic and Molecular Predictors of High Vancomycin MIC in Staphylococcus aureus Bacteremia Isolates - Holmes, Natasha E. (J Clin Microbiol, 2014)
An elevated vancomycin MIC is associated with poor outcomes in Staphylococcus aureus bacteremia (SAB) and is reported in patients with methicillin-susceptible S. aureus (MSSA) bacteremia in the absence of vancomycin treatment. Here, using DNA microarray and phenotype analysis, we investigated the genetic predictors and accessory gene regulator (agr) function and their relationship with elevated vancomycin MIC using blood culture isolates from a multicenter binational cohort of patients with SAB. Specific clonal complexes were associated with elevated (clonal complex 8 [CC8] [P < 0.001]) or low (CC22 [P < 0.001], CC88 [P < 0.001], and CC188 [P = 0.002]) vancomycin MIC. agr dysfunction (P = 0.014) or agr genotype II (P = 0.043) were also associated with an elevated vancomycin MIC. Specific resistance and virulence genes were also linked to an elevated vancomycin MIC, including blaZ (P = 0.002), sea (P < 0.001), clfA (P < 0.001), splA (P = 0.001), and the arginine catabolic mobile element (ACME) locus (P = 0.02). These data suggest that inherent organism characteristics may explain the link between elevated vancomycin MICs and poor outcomes in patients with SAB, regardless of the antibiotic treatment received. A consideration of clonal specificity should be included in future research when attempting to ascertain treatment effects or clinical outcomes.